Specific cell differentiation in breast cancer: a basis for histological classification. Issue 2 (28th July 2021) - Rakha, Emad; Toss, Michael; Quinn, Cecily
Abstract : Breast parenchyma progenitor cells show a high degree of phenotypic plasticity reflected in the wide range of morphology observed in benign and malignant breast tumours. Although there is evidence suggesting that all breast cancer (BC) arises from a common epithelial progenitor or stem cell located at the terminal duct lobular units (TDLUs), BC shows a broad spectrum of morphology with extensive variation in histological type and grade. This is related to the complexity of BC carcinogenesis including initial genetic changes in the cell of origin, subsequent genetic and epigenetic alterations and reprogramming that occur at various stages of BC development and the interplay with the surrounding microenvironment, factors which influence the process of differentiation. Differentiation in BC determines the morphology, which can be measured using histological grade and tumour type. Histological grade, which measures the similarity to the TDLUs, reflects the degree of differentiation whereas tumour type reflects the type of differentiation. Understanding BC phenotypic differentiation facilitates the accurate diagnosis and histological classification of BC with corresponding clinical implications in terms of disease behaviour, prognosis and management plans. In this review, we highlight the potential pathways that BC stem cells follow resulting in the development of different histological types of BC and how knowledge of these pathways impacts our ability to classify BC in diagnostic practice. We also discuss the role of cellular differentiation in producing metaplastic and neuroendocrine carcinomas of the breast and how the latter differ from their counterparts in other organs, with emphasis on clinical relevance.